Osseous Ilio-Trochanteric Bars as an Etiology of Hip Contracture in a Child with Congenital Contractures: A Case Report. Issue 4 (27th October 2022) - Cetik, Riza Mert; Aksoy, Taha; Yilmaz, Guney
Abstract : Case: A 5-month-old female patient presented with bilateral lower-limb deformities. Hips were fixed at 100° abduction, 15° flexion and 45° external rotation, flexion contracture in the knees, and bilateral teratologic equinovarus deformities. Radiographs revealed ilio-trochanteric osseous bars as the etiology of hip contractures. Staged surgeries were undertaken. At 4 years of age, she could stand upright with orthoses and sit without support. Conclusion: This is the first study to report bilateral congenital ilio-trochanteric osseous bars, which were resected without recurrence. Even with a very low potential of walking, release of the contractures allows for better function and possible wheelchair-dependent mobility in the future.